Correlative relationship of amounts of chlorophyll "a" and "b" pigments in plants with anthocyanin ridges L-2, L-3, F1, Fb, F2 (Texas Journal of Agriculture and Biological Sciences, 2023)
In the article: Based on the results of the experiments, the following scientific opinion is expressed. Experiments have shown that the separate actions of salinization and alkalization did not significantly affect the value of the ratio of chlorophyll a to chlorophyll b. The absence of significant changes in the value of this indicator indicates that these factors do not affect the light collection complex of the thylakoid membranes of this test crop.